JEJAK MISI ALLAH DALAM SEJARAH ISRAEL: TINJAUAN TEOLOGIS PERJANJIAN LAMA - Banya, Revisani; Metuduan, Oktovince; Yudas, Rindi; Soleman, Indri; Jauhari, Jhanet (PT. Giat Konseling Nusantara, 2025)
Some this paper explores the concept of missio Dei in the history of Israel as seen in the Old Testament stories. Using a qualitative theological approach and literature study, the article explains how God was involved in various stages of the history of His people from the call of kingdom and prophecy, to the time of exlle and the promise of restoration. God's active action in calling, accompanying, rebuking, and restoring His people is the main focus. From these stories, we can see that God's mission includes spiritual, social, and historical aspects that continue to be present in human life.